Working memory functioning in children with predominantly Inattentive Attention Deficit/Hyperactivity Disorder (ADHD) versus children with predominantly hyperactive ADHD - Allsopp, Karen Margaret (My University, 2009)
Abstract Working memory has been identified as an area in which children diagnosed with ADHD experience difficulty (Carnoldi, Marzocchi, Belotti, Caroli, De Meo & Braga, 2001). However, there are conflicting findings regarding the nature of working memory deficits in children diagnosed with ADHD and some researchers believe that working memory deficits may differ between the two ADHD subtypes (Diamond, 2005; Douglas, 2005; Knouse 2007; Milich , Balentine & Lynam, 2001). In addition, it is also thought that working memory may be one of the main contributing factors of this disorder (Rapport, Chung, Shore & Isaacs, 2001). Thus, there is clearly a need for additional and more detailed investigation into the way individuals with ADHD test with regard to their working memory functioning. This study attempted to examine the working memory functioning in children diagnosed with ADHD, in particular, the Predominantly Inattentive subtype and Predominantly Hyperactive/impulsive subtype in comparison to a control group. A sample of seventy-two participants was tested using the Ravens Progressive Coloured Matrices (RPCM) and the Automated Working Memory Assessment (AMWA) to assess their nonverbal intelligence and working memory. The primary motivating factor for the choice of participants was that they had to have been diagnosed by a professional as having ADHD (either subtype) and they had to be in Grades one or two. None of the children in the control group met the DSM-IV-TR (APA, 2000) criteria for ADHD. Repeated measures Abstract Working memory has been identified as an area in which children diagnosed with ADHD experience difficulty (Carnoldi, Marzocchi, Belotti, Caroli, De Meo & Braga, 2001). However, there are conflicting findings regarding the nature of working memory deficits in children diagnosed with ADHD and some researchers believe that working memory deficits may differ between the two ADHD subtypes (Diamond, 2005; Douglas, 2005; Knouse 2007; Milich , Balentine & Lynam, 2001). In addition, it is also thought that working memory may be one of the main contributing factors of this disorder (Rapport, Chung, Shore & Isaacs, 2001). Thus, there is clearly a need for additional and more detailed investigation into the way individuals with ADHD test with regard to their working memory functioning. This study attempted to examine the working memory functioning in children diagnosed with ADHD, in particular, the Predominantly Inattentive subtype and Predominantly Hyperactive/impulsive subtype in comparison to a control group. A sample of seventy-two participants was tested using the Ravens Progressive Coloured Matrices (RPCM) and the Automated Working Memory Assessment (AMWA) to assess their nonverbal intelligence and working memory. The primary motivating factor for the choice of participants was that they had to have been diagnosed by a professional as having ADHD (either subtype) and they had to be in Grades one or two. None of the children in the control group met the DSM-IV-TR (APA, 2000) criteria for ADHD. Repeated measures Abstract Working memory has been identified as an area in which children diagnosed with ADHD experience difficulty (Carnoldi, Marzocchi, Belotti, Caroli, De Meo & Braga, 2001). However, there are conflicting findings regarding the nature of working memory deficits in children diagnosed with ADHD and some researchers believe that working memory deficits may differ between the two ADHD subtypes (Diamond, 2005; Douglas, 2005; Knouse 2007; Milich , Balentine & Lynam, 2001). In addition, it is also thought that working memory may be one of the main contributing factors of this disorder (Rapport, Chung, Shore & Isaacs, 2001). Thus, there is clearly a need for additional and more detailed investigation into the way individuals with ADHD test with regard to their working memory functioning. This study attempted to examine the working memory functioning in children diagnosed with ADHD, in particular, the Predominantly Inattentive subtype and Predominantly Hyperactive/impulsive subtype in comparison to a control group. A sample of seventy-two participants was tested using the Ravens Progressive Coloured Matrices (RPCM) and the Automated Working Memory Assessment (AMWA) to assess their nonverbal intelligence and working memory. The primary motivating factor for the choice of participants was that they had to have been diagnosed by a professional as having ADHD (either subtype) and they had to be in Grades one or two. None of the children in the control group met the DSM-IV-TR (APA, 2000) criteria for ADHD. Repeated measures of Mann-Whitney and post-hoc analysis revealed that there were significant differences in the verbal short term memory, verbal working memory and visuospatial working memory between the three groups. Test results revealed no significant differences between the test scores of the Inattentive group and the control group in these areas. However, scores obtained by the Hyperactive/impulsive group differed significantly from those of the control and Inattentive groups. Score differences related specifically to verbal short term memory, verbal working memory and visuospatial working memory. This implies that children diagnosed with ADHD, (the Hyperactive/impulsive subtype) may need specific strategies in the classroom to enable them to encode, access and retrieve information to ensure optimal performance. The implications of these findings are discussed further in the thesis.
Keywords: working memory; ADHD; Attention Deficit Hyperactivity Disorder